Post a New Question

Trig

posted by .

Prove the equation is an identity :

csc3theta - csctheta + cottheta/csctheta = cotsqtheta + costheta

wow ... try that one

  • Trig -

    Here's where parentheses come in handy.

    As written, the identity is wrong. What you meant to say was

    (csc^3 - csc + cot)/csc
    = (csc(csc^2 - 1) + cot)/csc
    = (csc cot^2 + cot)/csc
    = csc cot^2/csc + cot/csc
    = cot^2 + cos/sin * sin
    = cot^2 + cos

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question